Enzymatic synthesis of d-alanine from a renewable starting material by co-immobilized dehydrogenases. (March 2018) - Li, Jianjiong; Chen, Xi; Cui, Yunfeng; Liu, Weidong; Feng, Jinhui; Wu, Qiaqing; Zhu, Dunming
Graphical abstract: Highlights: A green method was developed for the preparation of optically pure d -alanine from sodium pyruvate. A meso -diaminopimelate dehydrogenase and formate dehydrogenase were co-immobilized on a resin. The co-immobilized enzymes remained 80% of the initial activity after 12 reuses. d -alanine was obtained with 75.7% isolation yield and >99.5% ee for the first 20 batch reactions. Abstract: d -alanine is an important pharmaceutical intermediate. In this study, an effective method was developed to prepare optically pure d -alanine from sodium pyruvate with co-immobilized meso- diaminopimelate dehydrogenase from Symbiobacterium thermophilum and formate dehydrogenase from Candida Boidinii onto a resin. After optimizing the conditions of immobilization and biotransformation, the co-immobilized enzymes exhibited excellent stereoselectivity, yield and reusability. The co-immobilized enzymes kept 80% of its activity after 12 reuses, and d -alanine was isolated in 75.7% average yield and 99.5% ee for the first 20 cycles in the batch reactions. This suggests the co-immobilized enzyme system as a promising biocatalyst for the green production of d -alanine from pyruvic acid, a bio-based starting material.